National Strategic Projects and Human Rights Challenges in Merauke Regency, Indonesia - Muhamad Agung Prakoso; Mumuh Nurmatin (Civiliza Publishing, 2026)
The National Strategic Project (PSN) implemented in Merauke Regency, South Papua Province, aims to boost economic growth and equitable development through food and energy estate programs. However, at the implementation level, the massive wave of regulations facilitating land acquisition often triggers agrarian conflicts and alleged Human Rights (HAM) violations against local indigenous communities. This normative juridical legal research aims to analyze the root causes of the PSN implementation issues in Merauke and formulate a harmonious policy framework between national development and human rights protection. The study concludes that amidst the powerful legal instruments facilitating the project, limiting instruments do exist, such as the Human Rights Act, the Papua Special Autonomy Act, and the mechanism for filing lawsuits through the Administrative Court (PTUN) for disputes regarding Administrative Decisions. Harmonization between PSN development and the rights of Indigenous Peoples can be achieved if the development process implements the principle of Free, Prior, and Informed Consent (FPIC) as part of Human Rights Due Diligence, ensuring that the fulfillment of indigenous rights progresses in harmony with modern advancements